34 A lesion map of secondary bipolar disorder. Issue 8 (13th July 2017) - Barahona-Corrêa, Bernardo; Cotovio, Gonçalo; Ribeiro, Ricardo; Senova, Suhan; Silva, Vera Cruze; Oliveira-Maia, Albino J
Abstract : Objective: Bipolar Disorder (BPD) is a severe mood disorder, affecting 1.5%–4.4% of the population, and manifesting as an episodic, recurrent disturbance of mood, sleep, and behaviour. Secondary BPD (SBPD) develops following a brain insult, and is traditionally associated with right frontal lobe lesions. Yet, evidence supporting this association is mostly anecdotal. Here, we use two methodologies to study the neuroanatomy of SBPD: a systematic review of SBPD cases published in the literature, and reconstitution of brain lesions from a cohort of patients with SBPD in a single 3D template brain. Method: Systematic search of pubmed and WebOfScience for SBPD. For the lesion-map, data were collected from 16 consecutive patients (6 women, 10 men, mean age 60, 75±14, 27 years) with SBPD developing after an MRI-documented right-sided brain-lesion. For each scan we selected the sequence (T1, T2, or FLAIR) providing the best lesion discrimination. Lesions were manually segmented using MITK software. 1 After segmentation, each scan was co-registered onto a template reference brain 2 using 3DSlicer software. 3 Co-registration applies a transformation vector along the three axes of the source image, such that its voxels match the reference brain voxels to the highest possible degree. The resulting transformation vector was then applied to the image of each segmented lesion, and all the co-registered lesions were overlapped on the template brain scan (Automated anatomical labelling atlas or John Hopkins University white matter tractography Atlas for gray- and white-matter analysis, respectively). Results: 1476 articles were found in literature review, with 207 eligible cases, including 193 with focal brain lesions, mostly right-sided (84.5%) and more rarely left-sided (34.7%). Lesions were overrepresented in the frontal and temporal lobes bilaterally. In the 3D lesion-map, lesions were spread over the right hemisphere, with highest overlap in a medial area of the superior frontal gyrus (6 patients). Grey-matter quantitative mapping showed that the right superior frontal gyrus right anterior cingulate and supramarginal gyrus and right insula were lesioned in the highest number of patients (respectively 8, 7 and 6 patients). White-matter analysis highlighted the right superior longitudinal fasciculus and superior corona radiata (6 patients each), anterior corona radiata and body of corpus callosum (5 patients each). Conclusion: Our systematic review confirmed that right-sided frontotemporal lesions predominate in SBPD. In our cohort lesions converged on areas of the right executive control and anterior salience networks. Both have been implicated in the neurophysiology of primary BPD. 4, 5